De la critique du Capital à la micropolitique. L’héritage de Marx dans la pensée de Michel Foucault - Dimitri M’Bama (Astérion)
In this article, I explore the legacy of Karl Marx in Michel Foucault’s thinking. Focusing on such concepts as accumulation and discipline, reproduction and biopolitics, truth regime and ideology, askesis and revolution, I suggest four models allowing a deeper understanding of their controversial relationship: complementarity, confrontation, rejection, and reconciliation. As such, this study aims to offer “minority reading” against the neoliberal takes on Foucault, while showing how much his “alliance” with Marx would be an asset for contemporary left struggles.